Research on the influence of different heating zone lengths on pressure waves and a newly designed method of pressure wave mitigation in railway tunnels. (April 2022) - Wang, Junyan; Wang, Tiantian; Yang, Mingzhi; Qian, Bosen; Zhang, Lei; Tian, Xudong; Shi, Fangcheng
Highlights: Obtained the influence of the length of the heating zone on the peak value of the initial compression wave. Obtained the influence of the length of the heating zone on the peak value of the initial expansion wave. Study the effect of different heating zone lengths on the peak value of the train's initial compression wave. The result of the initial temperature field of the tunnel is obtained. Study the dynamic change process of temperature during train operation. Abstract: In this paper, through experimental and numerical simulation methods, the influence of the tunnel heating zone length on the pressure wave peak and temperature field changes is investigated in tunnels with different heating zone lengths. The accuracy of the applied simulation algorithm is verified against experimental data from moving model tests. Via numerical simulations, the changes in the pressure wave peak value and temperature field are explored with five heating zone lengths. For the compression wave, this research revealed that when LH (length of the heating zone) < LT (length of the train) and that with an increase in LH, the peak value of the initial compression wave notably decreases. When LH  > LT, the compression wave peak value remains basically stable. In regard to the expansion wave at tunnel measurement points, for L (from tunnel entrance) ⩽ 110 m, the initial expansion wave peak exhibits small fluctuations. At L > 110 m, with an increase in the heating zone length, the peak value of the expansion wave peak gradually decreases. In addition, the dynamic temperature field changes. The obtained research results provide a new idea to reduce the peak pressure value in a tunnel. In addition, this study provides a method for pressure wave mitigation during tunnel design and guidance for passenger comfort improvement in future city railway tunnels.